National Theatre and Epic Theatre: Creative Process of Una Hazaña Nacional - Santistevan De Noriega, Luis Alfonso (2025)
The author and director of Una hazaña nacional reflects on the experience of bringing an 18th-century historical figure to the stage, the use of primary and secondary sources, the selection and ordering criteria he used, and the theatrical aesthetics inspired by the documentary material. He also examines the relationship between fiction and history and the meaning of bringing past events into the present through theatre.